Clinical challenge: Deteriorating liver function in TB and HIV co-treatment - Francois Venter; Ntsakisi Masingi; Sarah Stacey; Sarah Fidler (AOSIS, 2013)
Editor's note: In this section of the Journal, we present complex, real-world HIV medicine cases to two experienced clinicians working in very different environments, and ask them to describe the approach that they would take if they saw the case in their local hospital setting. In our first edition, a patient with deteriorating liver function is presented by Prof. Francois Venter and Dr Ntsakisi Masingi, and then discussed by Dr Sarah Stacey in Johannesburg and Dr Sarah Fidler in London.